The in-vitro effects of E5555, a protease-activated receptor (PAR)-1 antagonist, on platelet biomarkers in healthy volunteers and patients with coronary artery disease - Serebruany, Victor L.; Kogushi, Motoji; Dastros-Pitei, Daniela; Flather, Marcus; Bhatt, Deepak L. (Thrombosis and Haemostasis, 2009)
E5555 is a potent protease-activated receptor (PAR-1) antagonist targeting the G-coupled receptor and modulating thrombinplatelet-endothelial interactions. The drug is currently being tested in phase II trials in patients with coronary artery disease (CAD) and has potential antithrombotic and anti-inflammatory benefits.We investigated the in-vitro effects of E5555 on platelet function beyond PAR-1 blockade in healthy volunteers and CAD patients treated with aspirin (ASA) with or without clopidogrel. Conventional aggregation induced by 5 µM ADP, 1 µg/ml collagen, 10 µM TRAP, whole blood aggregation with 1 µg/ml collagen, and expression of 14 intact, and TRAP-stimulated receptors by flow cytometry were utilised to assess platelet activity after preincubation with escalating concentrations of E5555 (20 ng/ml, 50 ng/ml, and 100 ng/ml) in healthy volunteers, CAD patients treated with ASA, and CAD patients treated with ASA and clopidogrel combination (n=10, for each group). E5555 inhibited a number of platelet biomarkers. Platelet inhibition was usually moderate, present already at 20 ng/ml, and was not seemingly dose-dependent without TRAP stimulation. E5555 caused 10–15% inhibition of ADP- and collagen-induced platelet aggregation in plasma, but not in whole blood.TRAP-induced aggregation was inhibited almost completely. PECAM-1, GP IIb/IIIa antigen, and activity with PAC-1, GPIb, thrombospondin, vitronectin receptor expression, and formation of platelet-monocyte aggregates were also significantly reduced by E5555.TRAP stimulation caused dose-dependent effects between 20 and 50 ng/ml E5555 doses. P-selectin, LAMP-1, LAMP, and CD40-ligand were not affected by E5555. In conclusion, E5555 in vitro moderately but significantly inhibits platelet activity beyond PAR-1 blockade. Antiplatelet potency of ASA alone, and the combination of ASA and clopidogrel may be enhanced by E5555 providing rationale for their synergistic use. Selective blockade of platelet receptors suggests unique antiplatelet properties of E5555 as a potential addition to current antithrombotic regimens.
Keywords: E5555; PAR-1; thrombin receptor antagonists; platelets; aspirin; clopidogrel; in vitro; coronary artery disease